Environmental threats to children's health – a global problem. (27th October 2008) - Neira, Maria; Gore, Fiona; Brune, Marie-Noel; Hudson, Tom, Jenny Pronczuk de Garbino
Today's children are exposed to a wide range of environmental threats, whose consequences on health and development may appear early in life, throughout their youth and even later, in adulthood. Health problems linked to environmental hazards are multiplying and becoming more visible due to a rapidly changing environment, rapid population growth, overcrowding, fast industrialisation and uncontrolled pollution from many anthropogenic and also natural sources, and as a result of the effects of climate change. A World Health Organization report on the global burden of disease estimated that nearly a quarter of the global disease burden is related to environmental causes. These environmental-mediated diseases cause more than three million deaths in children under five every year. Such a large burden is unacceptable. Both industrialised and developing countries should reinforce their capacities to assess the environmental burden of paediatric diseases and characterise their impact on children's health. This will enable all responsible sectors to distinguish the main environmental threats affecting children's health and identify their specific roles in improving children's environments. Implementing these activities and turning efforts into prevention, education, policy-making and other actions will reduce the burden of disease affecting children globally, therefore contributing towards achieving the Millennium Development Goals (MDGs).